Seasonality of Coliform Bacteria Detection Rates in New Jersey Domestic Wells. Issue 3 (24th October 2016) - Atherholt, Thomas B.; Procopio, Nicholas A.; Goodrow, Sandra M.
Abstract: It is important that indicators of fecal pollution are reliable. Coliform bacteria are a commonly used indicator of fecal pollution. As other investigators have reported elsewhere, we observed a seasonal pattern of coliform bacteria detections in domestic wells in New Jersey. Examination of a statewide database of 10 years of water quality data from 93, 447 samples, from 78, 207 wells, generated during real estate transactions, revealed that coliform bacteria were detected in a higher proportion of wells during warm weather months. Further examination of the seasonal pattern of other data, including well water pH, precipitation, ground and surface water temperatures, surface water coliform bacteria concentrations, and vegetation, resulted in the hypothesis that these bacteria may be derived from nonfecal (or environmentally adapted) as well as fecal sources. We provide evidence that the coliform seasonality may be the result of seasonal changes in groundwater extraction volumes (and to a lesser extent precipitation), and temperature‐driven changes in the concentration of surface or near‐surface coliform sources. Nonfecal coliform sources may not indicate the presence of fecal wastes and hence the potential presence of pathogens, or do so in an inconsistent fashion. Additional research is needed to identify the sources of the coliforms detected in groundwater. Abstract : Article impact statement : The usefulness of coliform bacteria as indicators of fecal pollution of groundwater may be weakened by a seasonal difference in detection rates.